Effects of an 8-Week Aerobic Exercise Program on Some Indicators of Oxidative Stress in Elderly Women - Keyvan Hejazi; Mahdi Ghahremani Moghaddam; Teimour Darzabi (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives Oxidative stress has an important role in the pathogenesis of diseases such as cardiovascular disease, cancer, diabetes and aging. The present study investigated the effects of 8 weeks of aerobic training on 8-hydroxy-2'-deoxyguanosine and body composition in elderly women. Methods & Materials This was a quasi-experimental study. The study participants were selected by convenience sampling method. In total, 21 subjects with the age range of 60-70 years were assigned into 2 groups (experimental [n=11] and control [n=10]). The 8-week aerobic training program were demonstrated 3 sessions a week, for 45-60 minutes per session, with the intensity of 50% to 70% of maximum heart rate. The blood samples were obtained 24 hours after the intervention to measure the serum levels of 8-OHdG. For comparison of within and between group mean scores, Paired t test and Independent samples t test were used, respectively. Results Eight weeks aerobic training significantly reduced the weight, BMI and body fat percentage in elderly women. Moreover, the levels of serum 8-OHdG after an 8 weeks aerobic training significantly reduced. However, the levels of 8-OHdG urine reduced at the end of the training, but it was non-significant. There were significant differences between active and inactive elderly woman in terms of weight and serum 8-OHdG variables. Conclusion This study suggests that aerobic training decreases serum 8-OHdG. Regular aerobic physical activity with moderate intensity improves the body anti-oxidative capacity and can prevent the incidence of atherosclerosis disease.